Maastricht Overcome: An Evolving Disconnect Between the ECB’s Power and Independence - Anna-Lena Högenauer; Joana Mendes (Politics and Governance)
In the course of the last two decades, the legitimacy of the European Central Bank (ECB) has withered as monetary policy has become more politicized. This editorial places these debates in the context of the literature on central bank independence. Many critical voices warned—long before the crisis—that the ideal of highly independent central banks with narrow technocratic mandates would not work in the long term and would come under particular pressure during periods of instability. Indeed, after over a decade of ongoing crisis, the ECB’s functions have expanded considerably, which in turn altered its relationship with other institutions and its role in the economic and political system of the European Union. In particular, the ECB’s activities during the eurozone crisis, new debates on whether the ECB should support political goals like the fight against climate change, and its participation in geopolitical stand-offs have brought its political role clearly to the fore. Crucially, this evolution challenges the ECB’s high degree of independence, as decisions that are closely related to political debate also require stronger political (democratic) legitimacy and legal accountability.